What is the stock of the situation? A bibliometric analysis on social and environmental accounting research in public sector. Issue 1 (6th June 2018) - Fusco, Floriana; Ricci, Paolo
Abstract : Purpose: The purpose of this paper is to provide a picture of the state of the art in social and environmental accounting research applied to the public sector, highlighting different streams and the main gaps in current literature and providing input for future research. Design/methodology/approach: A bibliometric method was used to analyse the characteristics, citation patterns and content of 38 papers published in international academic journals. Findings: The findings show that the research on social and environmental reporting in the public sector is still at an early stage. Current investigations, although slowly on the increase, are still very few and localised. Most papers are about the reasons why public organisations report, what and how they report, but there are so many aspects that need to be investigated more in-depth or require extra validation in order to open new directions for future research, among which the relationship with and the differences between other non-financial type of reporting, namely ICR and IR. Research limitations/implications: The study shows some limitations, mainly related to the adoption of the bibliometric method. Indeed, it does not take into account books and chapters but only papers published in international and academic journals. This leads to exclude a significant part of the existing literature and other relevant contributions on the field. Originality/value: Social and environmental reporting practices are quickly spreading in the public sector. The field is particularly interesting, given the specific connotations of this kind of organisations. However, the literature is clearly not exhaustive and there is not a comprehensive and systematic review of the state of the art on the subject.